An intrinsic agonist mechanism for activation of glucagon-like peptide-1 receptor by its extracellular domain - Yin, Yanting (Cell Discov, 2016)
The glucagon-like peptide-1 receptor is a class B G protein coupled receptor (GPCR) that plays key roles in glucose metabolism and is a major therapeutic target for diabetes. The classic two-domain model for class B GPCR activation proposes that the apo-state receptor is auto-inhibited by its extracellular domain, which physically interacts with the transmembrane domain. The binding of the C-terminus of the peptide hormone to the extracellular domain allows the N-terminus of the hormone to insert into the transmembrane domain to induce receptor activation. In contrast to this model, here we demonstrate that glucagon-like peptide-1 receptor can be activated by N-terminally truncated glucagon-like peptide-1 or exendin-4 when fused to the receptor, raising the question regarding the role of N-terminal residues of peptide hormone in glucagon-like peptide-1 receptor activation. Mutations of cysteine 347 to lysine or arginine in intracellular loop 3 transform the receptor into a G protein-biased receptor and allow it to be activated by a nonspecific five-residue linker that is completely devoid of exendin-4 or glucagon-like peptide-1 sequence but still requires the presence of an intact extracellular domain. Moreover, the extracellular domain can activate the receptor in trans in the presence of an intact peptide hormone, and specific mutations in three extracellular loops abolished this extracellular domain trans-activation. Together, our data reveal a dominant role of the extracellular domain in glucagon-like peptide-1 receptor activation and support an intrinsic agonist model of the extracellular domain, in which peptide binding switches the receptor from the auto-inhibited state to the auto-activated state by releasing the intrinsic agonist activity of the extracellular domain.